Designing of Parking Spaces on Parking Taking into Account the Parameters of Design Vehicles - Miroslava Mikusova; Jamshid Abdunazarov; Joanna Zukowska; Juraj Jagelcak (Computation, 2020)
Nowadays, in all cities, there is an acute problem of a lack of parking spaces. The number of vehicles is constantly increasing not only in big cities and megacities, but also in small towns of the country, and there are not enough parking places—the pace of solving the problem is several times slower than the growth rate of transport among citizens. The paper is dedicated to the determination of an optimal size of a parking place for design vehicles in a parking space as an element of roads. In the example of passenger cars and trucks, the optimal number of parking places is presented. The results of the research on the dimensioning of parking spaces serve as recommendations and can be used for the design of objects of transportation infrastructure. According to the research, authors introduce the term “design vehicle” and provide its definition. They also figure out optimal parameters for each design vehicle and recommend a special template for designing parking places.